Kinetic and thermodynamic analyses for pyrolysis of hemp hurds using discrete distributed activation energy model. (March 2022) - Mankeed, Panuphong; Onsree, Thossaporn; Naqvi, Salman Raza; Shimpalee, Sirivatch; Tippayawong, Nakorn
Abstract: In many counties, hemp is becoming a high-valued economic crop. Post-processing, more than 65% w/w of its starting material becomes waste. Herein, pyrolysis of hemp hurds/residues was investigated under low (10–50 °C/min) and intermediate (100–150 °C/min) heating rates using a discrete distributed activation energy model (DAEM). Thermochemical decomposition of hemp hurds occurred in three stages: drying, active pyrolysis, and char formation, accounting for 70–80% w/w overall weight loss. With the discrete DAEM, the model can be utilized for predicting pyrolysis behaviors of hemp hurds accurately with correlation coefficient of over 0.99. Different reaction mechanisms appeared between the low and intermediate heating rates with 60 and 25 parallel first-order pyrolytic reactions detected, respectively. Under low heating rates, the pyrolysis showed high reactivity. The activation energy ( E ) and enthalpy change ( Δ H ) varied within 240–320 kJ/mol. The Gibbs free energy ( Δ G ) was 120–200 kJ/mol. The entropy change ( Δ S ) was 120–300 J/mol∙K. Under intermediate heating rates, the reactions were close to thermodynamic equilibrium and stability. The E and Δ H fluctuated from 80 to 250 kJ/mol. The Δ G was within 160–200 kJ/mol. The Δ S was between −100 and 100 J/mol∙K.